2014
DOI: 10.1002/bab.1151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of butyrate‐induced production of a mannose‐6‐phosphorylated therapeutic enzyme using parallel bioreactors

Abstract: Bioreactor process changes can have a profound effect on the yield and quality of biotechnology products. Mannose-6-phosphate (M6P) glycan content and the enzymatic catalytic kinetic parameters are critical quality attributes (CQAs) of many therapeutic enzymes used to treat lysosomal storage diseases (LSDs). Here, we have evaluated the effect of adding butyrate to bioreactor production cultures of human recombinant β-glucuronidase produced from CHO-K1 cells, with an emphasis on CQAs. The β-glucuronidase produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…7A). These data are in agreement with previous observations and corroborate that glycosylation of GUS renders it larger leading to longer migration time than non-glycosylated proteins of similar size [10]. Analysis of CE-SDS under non-reducing conditions showed that GUS samples purified by both methods have monomers and dimers, indicating the occurrence of inter-molecular disulfide bonds (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…7A). These data are in agreement with previous observations and corroborate that glycosylation of GUS renders it larger leading to longer migration time than non-glycosylated proteins of similar size [10]. Analysis of CE-SDS under non-reducing conditions showed that GUS samples purified by both methods have monomers and dimers, indicating the occurrence of inter-molecular disulfide bonds (Fig.…”
Section: Resultssupporting
confidence: 92%
“…GUS activity was measured using a high throughput assay at 25 °C with PNPG substrate as described before [10]. The formation of para -nitrophenol (PNP) was measured at 405 nm in a Synergy H1 Multi-Mode Reader (BioTek Instruments, Inc., Winooski, VT).…”
Section: Methodsmentioning
confidence: 99%
“…The signal intensity was integrated in each of the three sections; the integrated intensity of the GUS band was divided by the sum of the integrated intensities of the entire lane, producing the fractional amount of the total protein consisting of GUS, which is expressed as percent purity. The percent purity was then used to correct the eLuminol-staining measurements, yielding the amount of GUS present per well (Figure 2D), which was comparable to the amount of protein independently determined by a capillary electrophoresis method previously reported (16). Finally, to determine the average number of phosphorylation sites, the calculated amount of phosphorylated protein was divided by the corrected amount of GUS protein to determine the number of phosphates per molecule (Figure 3, gray bars).…”
Section: Methodssupporting
confidence: 60%
“…Recombinant human GUS was produced from a CHO-K1 cell line as reported previously (16). Unpurified GUS from the spent media was either dialyzed against buffer (10 mM Tris-HCl, pH 8.0, with 10% glycerol) or purified as described previously (17).…”
Section: Methodsmentioning
confidence: 99%
“…A balance must be struck between product yield and consistency of critical biochemical quality attributes. Factors that influence cell growth, physiology, and subsequently affect protein yield include: bioreactor process parameters (e.g., temperature, dissolved oxygen (DO), pH, agitation), nutritional supplementation (e.g., glucose, amino acids, cortisone), and the addition of chemical induction factors (e.g., butyrate). Yet changes in these same factors can adversely affect product quality, for example, by altering the distribution of charge variants or glycoforms and can even lead to product crystallization .…”
Section: Introductionmentioning
confidence: 99%